Effect of different adhesive strategies and storage time on bond strength of bi-functional monomers to simulated endodontically-treated dentin - Girotto, Aline Carvalho [UNESP]; Abuna, Gabriel; Sanchez-Puetate, Cristian [UNESP]; Piccioni, Mayra Andressa [UNESP]; Porto, Thiago Soares; Kuga, Milton Carlos [UNESP] (Japanese Society for Dental Materials and Devices, 2021)
Adhesive strategies were evaluated on the bond strength of bi-functional monomers bonded to endodontically-treated-dentin (ETD). Superficial dentin was removed on human molars. Teeth were immersed in 5 mL 2.5% NaOCl, followed by immersion in 5 mL 17% EDTA. Dentin surface impregnated with epoxy resin-based sealer was then divided four groups (n=10): Scotchbond Multi-Purpose (SBMP); Single Bond Universal (SBU); Optibond All-in-One (OPB); and Tetric-N-Bond Universal (TBU). After 24-h or 1-year-of-storage specimens were submitted to microtensile bond strength (µTBS) and failure classification. A confocal laser scanning microscope (CLSM) evaluated the hybrid layer formation. Two-way ANOVA and Tukey-HSD test were performed (α=5%). The µTBS did not present statistical differences among adhesive strategies after 24-h. Significant differences were found after 1-year-of-storage. CLSM analysis showed water infiltration and consequently degradation of the hybrid layer after 1-year-of-storage. The use of SBU universal adhesive on the self-etching mode on ETD produced more stable bond over the 1-year-of-storage.
Keywords: Adhesives; Endodontically-treated-dentin; Microtensile; Self-etching